From Conscious Values to Tacit Beliefs: Assessing Parsons’ Influence on Contemporary Sociology - Williams, Lawrence Hamilton (Frontiers in Sociology, 2017)
Much sociological research is now focused on demonstrating how culture both motivates individuals to act and provides them with justifications for their actions (see Vaisey 2009). However, I argue that this sociological work relies on a model of action that sees culture itself as driving action beyond individuals’ reflexive use of culture. I argue that it does so by conceptualizing the internalization of culture as pre-subjective and impersonal, essentially committing what is often deemed the Parsonian problem of diminishing the contingent nature of social action through the use of abstractions. Just as Parsons was charged with placing undue emphasis on various social systems rather than on persons, dominant strands of sociological inquiry overemphasize the salience of shared norms and schemas at the cost of individual perception. The major difference, however, is that while Parsons justified his focus on the system-level by framing individuals as highly conscious and deliberate in their actions, contemporary sociologists tend to frame individuals’ actions as largely unconscious and reliant on situational logics. In doing so, the consciously and normatively overdetermined actor in Parsonian sociology is now unconsciously and situationally overdetermined in contemporary sociology, a perspective ironically anticipated and deliberately positioned against by Parsons himself. Thus, I assert that efforts to de-Parsonize the discipline have given rise theoretical problems that need resolution. I demonstrate how utilizing some of Parsons’ key insights on the importance of simultaneously considering multiple levels of analysis when studying action could be a fruitful way to proceed.